Pola Penggunaan Obat pada Pasien Rawat Intensif di RSUD Arifin Achmad Provinsi Riau - Oktadiani, Dela; Fauzia, Dina; Muharrami, Vera (Jurnal Ilmu Kedokteran, 2024)
Critically ill patients in the ICU have organ dysfunction, so they are dependent on sophisticated equipment, monitoring, and therapy. One of the types of treatment in the ICU is medication. The aim is to observe the pattern of drugs in patients in ICU Arifin Achmad General Hospital. This study is a descriptive retrospective with secondary data from medical records. One hundred fifty samples fulfilled the inclusion criteria. Profiled patients in the ICU are male, comparable to female patients (48,7%: 51,3%). The common groupage that is hospitalized in the ICU is 56-65 years old (22,6%). Length of stay is 1-7 days (68%). JKN is the most widely used for payment (72.7%). Eighty-five patients were improved and moved to other rooms (56.7%). The primary cause of admission in ICU is post-surgery (22%). Anti-infection was the most prescribed category of medication (18.8%). The number of prescriptions is 6-10 drugs (40.7%). Parenteral administration is the most common route for administration (85.74%). Duration of therapy is 1-7 days with the number of 1289 drugs (94%).